OPTIMIZATION OF IMMEDIATE RELEASE TABLET OF RALOXIFENE HYDROCHLORIDE BY WET GRANULATION METHOD (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Population explosion is a major problem it is raising tremendously; this may affect drastically the economic growth. So family planning has been promoted through several methods of contraception. A wide variety of synthetic contraceptive agents are available, but these cannot be used continuously due to their side effects. Thus the present study was to evaluate the effect of Bougainvillea spectabilison fertility of male and female mice. Swiss Albino mice were orally administered with aqueous crude extract of the leaves of Bougainvillea spectabilis (800 mg/kg of body weight/day, for 30 days), and effect of crude extract on reproductive organs and fertility was investigated. The treatment Caused decrease in weight of testis, sperm count and the histological examination revealed a reduction in the size of seminiferous tubules along with the thickness of germinal epithelial cells, though some of the epithelial cells and interstitial cells of leydig showed hypertrophy. Moreover, the lumen of the tubules was found to be devoid of sperms. On the other hand, in treated females no histological changes could be observed. The only marked change, which could be visualized, was the slight disruption of estrous cycle having prolonged metaestrus phase, which has been increased by 145.28 %. The overall duration of estrous cycle had been extended by more than one day. The hormonal profile was also influenced by the Bougainvillea spectabilis extract. The testosterone and estrogen levels were significantly decreased.